Pengaruh Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 3 Praya - Sapira, Isni; Mawarzani, Sapka; Adipta , Marazaenal (Universitas Qamarul Huda Badaruddin, 2023)
This study aims to determine the effect of the Think Pair Share (TPS) learning model on the learning outcomes of tenth-grade students at SMA Negeri 3 Praya. The background of this research is the low learning achievement caused by the dominance of lecture methods and the lack of active student involvement in the learning process. A pre-experimental one-group pretest-posttest design was employed, with a sample of 32 students selected using purposive sampling. The instrument was a 25-item multiple-choice test. The results showed an increase in the average score from 48.75 in the pretest to 69.5 in the posttest. The Paired Sample T-Test revealed a significance value of 0.000 (<0.05), indicating a significant effect of TPS on students’ learning outcomes. Therefore, the TPS model is effective in improving student learning outcomes.